Geographical phenotypic variation and reproductive system of a distylous Rubiaceae in the brazilian cerrado - Doria, Maria Júlia Waldemarin [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Palicourea rigida is a Rubiaceae species widely distributed across the Brazilian Cerrado. The species presents distyly, a type of floral dimorphism comprised of two floral morphs that are followed by a genetic heteromorphic self-incompatibility that enables the reproduction only after pollen flow between the distinct floral morphs. Palicourea rigida is typically pollinated by hummingbirds and has flowers varying in the color spectrum between orange and red. The species, however, presents a phenotypic variation across its distribution, and this variation includes floral size, color, and life form. In the southernmost distribution of the Cerrado vegetation, P. rigida presents a notoriously phenotypic variation with a markedly different life form, flower size, and color. In this sense, considering the phenotypic variation in Palicourea rigida populations either in life form and floral traits, as well as its dependence on pollinators for sexual reproduction, in this study we described the changes in the floral morphology of different populations of P. rigida and tested if they are followed by alterations of the basal features of distyly, i.e., breakdown of the heteromorphic self-incompatibility system, reciprocal hercogamy and isoplethy. Additionally, due to the change in flower color and size, we discussed the hypothesis of a potential pollinator shift from hummingbirds (ornithophily) to bees (melitophilly) in the dwarf population presenting yellow flowers as a possible outcome of pollinator-mediated selection. For this, we perform controlled pollination experiments in the southernmost dwarf population, analyzed the floral morphology, and evaluate floral color and pollinator perception. Our results showed that the basal features of distyly were maintained in the southernmost dwarf population, and the flowers are significantly smaller, with a larger stigmatic lobe in both floral morphs. Our results reinforce the role of inaccuracy in legitimate pollen deposition, where the higher inaccuracy in high organs seems to be responsible for lower pollen deposition at that level. Besides that, we found a pollinator shift from hummingbirds to bees in the population, even with no cognitive difference for bees when exposed to P. rigida yellow and reddish flowers.

Palicourea rigida é uma espécie de Rubiaceae amplamente distribuída no Cerrado brasileiro. A espécie apresenta-se distilia, um tipo de dimorfismo floral composto por dois morfos florais seguidos por uma autoincompatibilidade heteromórfica genética que possibilita a reprodução somente após o fluxo de pólen entre os distintos morfos florais. Palicourea rigida é tipicamente polinizada por beija-flores e possui flores que variam no espectro de cores entre laranja e vermelho. A espécie, no entanto, apresenta uma variação fenotípica ao longo de sua distribuição, e essa variação inclui tamanho floral, cor e forma de vida. Na distribuição mais ao sul da vegetação do Cerrado, P. rigida apresenta uma variação notoriamente fenotípica com uma forma de vida, tamanho de flor e cor marcadamente diferentes. Nesse sentido, considerando a variação fenotípica em populações de Palicourea rigida tanto na forma de vida quanto nos caracteres florais, bem como sua dependência de polinizadores para a reprodução sexuada, neste estudo descrevemos as mudanças na morfologia floral de diferentes populações de P. rigida e testados se eles são seguidos por alterações das características basais de distilia, ou seja, quebra do sistema heteromórfico de auto-incompatibilidade, hercogamia recíproca e isopletia. Além disso, devido à mudança na cor e no tamanho das flores, discutimos a hipótese de uma mudança potencial do polinizador de beija-flores (ornitofilia) para abelhas (melitofilia) na população de anãs apresentando flores amarelas como um possível resultado da seleção mediada por polinizadores. Para isso, realizamos experimentos de polinização controlada na população de anões mais ao sul, analisamos a morfologia floral e avaliamos a cor floral e a percepção do polinizador. Nossos resultados mostraram que as características basais de distilia foram mantidas na população anã mais ao sul, e as flores são significativamente menores, com um lobo estigmático maior em ambos os morfos florais. Nossos resultados reforçam o papel da imprecisão na deposição legítima de pólen, onde a maior imprecisão em órgãos altos parece ser responsável pela menor deposição de pólen naquele nível. Além disso, encontramos um deslocamento do polinizador de beija-flores para abelhas na população, mesmo sem diferença cognitiva para as abelhas quando expostas a flores amarelas e avermelhadas de P. rigida.
Geographical phenotypic variation and reproductive system of a distylous Rubiaceae in the brazilian cerrado
Keywords: Ecologia; Palicourea rigida; Polinização